Fetoplacental Hydrops: A Case of Recurrent Fetal Hydrops and Review of the Literature - Ben Mohamed, Khaoula; Medemagh, Malak; Cheikh Mohamed, Chayma; Lazreg, Hanan; Toumi, Dhekra; Raja, Faleh (Gynecology Obstetrics & Reproductive Medicine, 2025)
Recurrent fetal hydrops is a severe condition with a generally poor prognosis. The causes of fetal hydrops are diverse and mainly classified as immunological or non-immunological, although genetic and metabolic factors contribute to the recurrent form. Maternal prognosis is also at risk due to the association of this condition with severe preeclampsia. For women with a history of pregnancy complicated by fetal hydrops, subsequent pregnancies require special monitoring to detect early ultrasound signs of recurrence. We report a case of recurrent hydrops fetalis, which represents the fourth episode. This case emphasizes the importance of etiological diagnosis, particularly genetic causes, to provide appropriate genetic counseling and prevent transmission to future generations.